The Maori perspective of the news : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Business Studies in Communication Management at Massey University - TeAwa, Joanna Ngani (Massey University, 1996)
The Maori perspective of the news has been identified by Fox (1998, 1992, 1993) and Walker (1994), but the dynamics of the presentation and construction of the Maori perspective of the news had not been well defined. This research attempted to define and distinguish the differences between the news produced by Mana News from the news produced by mainstream organisations. In particular the selection of what issues and events became news and how they became news was examined, as well as a study of the end product heard by the listeners. Two methodologies were employed; participant observation and content analysis. Participant observation explored the decision-making process in the manufacture of news. This methodology gives the research an "insider" nature. The participant observation identified the news values used in the selection of news and contrasted these values applied in Mana News to those identified by Galtung and Ruge (1965) and Masterton (1994). The inter-play between the journalists and sources was also explored. Content analysis methodology complements the participant observation methodology. Essentially content analysis is a research that focuses on the finished product, and examines what is published or broadcasted after the complex inter-play of relationships between the source and journalist which influences news creation. The content analysis examined numerous theories that may help identify the difference in the construction and presentation between the Maori perspective and the traditional mainstream perspective of the news. Journalism development identified by Loo (1994) was explored, as was the dialectical story model, the tone and nature of the stories and the diversity of sources. Overall the results identified some fundamental differences in the application of news values, the utilisation of sources, the types of sources used, and the nature and tone of stories. The findings also have revealed a journalistic genre that appears to be a more appropriate way of categorising the writing style used in Mana News, as opposed to the traditional 'hard' and 'soft' news categories which characterises conventional journalistic writing. The research moved beyond saying that there is a difference between Mana News and mainstream news media and identified how it is different. Finally, considering this defined difference in perspectives, the socio-political and legislative implications and the commitment broadcasters have to race relations was explored. Change to New Zealand broadcasting policy and legislation was recommended.
Keywords: Ethnic attitudes; New Zealand; Maori (New Zealand people); Mass media and race relations; Reporters and reporting; Māori Masters Thesis; Research Subject Categories::SOCIAL SCIENCES